2018
DOI: 10.1016/j.gaitpost.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Experience does not influence injury-related joint kinematics and kinetics in distance runners

Abstract: Increased years of running experience does not appear to significantly influence running mechanics. However, age and running speed do influence biomechanical variables associated with injury in distance runners. Thus, there may be factors, other than running mechanics, that contribute to less risk in more experienced runners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
5
15
1
Order By: Relevance
“…However, in this study, novice runners observed larger knee flexion than experienced runners [ 31 ]. The ROM of the knee joint was larger in the novice runners than experienced runners, and this finding is in agreement with Agresta et al [ 32 ]. This could be attributed to novice runners having poor running mechanics, which results in higher loads on musculoskeletal tissue, especially at the tibia and the knee.…”
Section: Discussionsupporting
confidence: 92%
“…However, in this study, novice runners observed larger knee flexion than experienced runners [ 31 ]. The ROM of the knee joint was larger in the novice runners than experienced runners, and this finding is in agreement with Agresta et al [ 32 ]. This could be attributed to novice runners having poor running mechanics, which results in higher loads on musculoskeletal tissue, especially at the tibia and the knee.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies suggest that running experience does not influence running biomechanics. Agresta et al (2018) did not find any influence of years of running experience in trunk and lower limb kinematics, spatiotemporal variables, nor GRF variables during running. Similarly, Schmitz et al (2014) did not find differences between novice and experienced runners in impact peak, loading rate, nor peak hip adduction angle during running.…”
Section: Introductioncontrasting
confidence: 58%
“…Consistent with the previous report that altered movement control strategies may be developed with increased running experience, thus optimizing task performance [10], [25]. A further evidence of adjust-ing capability in the speed recovery of experienced elite runners concluded that experienced runners could recover to normal speed faster than novice runners after the interference of running speed [1].…”
Section: Discussionsupporting
confidence: 84%
“…Agresta et al [1] found no correlation between increased running experience and injury prevention. However, van Gent et al [25] indicated that runners usually suffered from injuries to the feet, and running experience could effectively reduce the risk of injury.…”
Section: Discussionmentioning
confidence: 96%